Pengembangan Sistem Inventory dan Sistem Pengiriman Barang untuk Memajukan Usaha PT. ABC - Wilson, Arthur; Rarasati, Dionisia Bhisetya (Jurnal Ilmiah Sains dan Teknologi, 2024)
In a company, there are always inbound and outbound goods. To record and track the movement of these goods efficiently, a system is needed. Manual writing is no longer feasible due to the high volume and rapid movement of goods, increasing the likelihood of errors. Therefore, an inventory system that automatically records the movement of goods is necessary to minimize human errors. There are systems for both inbound and outbound goods. All goods entering and leaving the company must be recorded for reporting purposes. For sales and shipment of goods, a shipment system is essential to make deliveries more efficient, timely, and cost-effective. The inventory system aims to record the movement of goods. Additionally, the shipment system cannot track the current status of shipments. The goal of this research is to develop inventory and shipment systems that can assist PT ABC's operations and facilitate its growth.